Post-Expansion and end of treatment outcomes of semi-rapid maxillary expansion with a modified removable appliance - Alka M Banker; Malvi N Thakkar; Bhagyashree B Desai; Sarandeep S Huja (Wolters Kluwer Medknow Publications, 2022)
Context: Maxillary expansion is the mainstay therapy for maxillary transverse deficiency. There has been a constant search for the most effective yet biologically friendly method of maxillary expansion, alternatives being, slow, rapid and semi rapid. Aims: The purpose of this study was to explore the outcome of palatal expansion achieved using a removable plate and low continuous forces brought about by a semi rapid screw activation protocol. Settings and Design: Retrospective study. Methods and Material: Plaster models of 56 consecutive patients treated for maxillary expansion were obtained pre-treatment (T0), post-expansion (T1), and post fixed appliance treatment (T2). The radiographic images of the models were traced using Image J software. Linear and angular measurements were evaluated to measure transverse change. Statistical Analysis Used: Interclass Correlation Coefficient [ICC] and Dahlberg's formula were used for reliability test. The differences in the mean values between the three duration groups [T0, T1 and T2] were analysed using Analysis of Variance (ANOVA). For multiple comparisons, a post hoc Tukey honestly significant difference (HSD) test was performed. Results: Significant increase in inter-molar, alveolar and palatal linear widths were observed from T0 to T1 with significant relapses from T1 to T2, with an overall net gain remaining at T2. Similarly, significant increases in all angular measurements were observed from T0 to T1 with significant relapses from T1 to T2 and an overall insignificant change at T2 as compared to T0. Conclusion: The appliance and protocol were effective in producing transverse expansion with minimal molar and alveolar tipping.